Development of Stilling Basin Model at Zero Depth of Pipe Outlet to Basin Floor: An Advanced Research - Tiwari, H. L.; Hora, M. S. (New Approaches in Engineering Research Vol. 16, 2021)
In this chapter, study of new Stilling Basin Model have been carried out for non-circular pipe outlet keeping the outlet at zero depth from the basin of floor. Evolution was carried out after testing of twenty four models using different appurtenances like impact wall, intermediate sill and end sill. Testing of Stilling Basin Model have been performed for non-circular pipe outlet with Froude number 3.85. All models were experimented using same bed materials and tail water depth was kept constant as normal depth and test duration was kept constant as forty five minutes for all models. After test run of forty minutes duration Scour parameters were measured and performance of model were measured by computing Scouring index. The Scour indexes after the end sill were estimated for each test run. After experimentation, it was found that new developed stilling basin model with appurtenances of rectangular intermediate sill of cross section 0.5 d width and 1d height, impact wall of dimensions 1 d x 2.2 d and a triangular end sill of cross section 1 d width and 1 d height at basin length of 6.4 d performed better as compared to other tested models with zero depth of pipe outlet from basin floor. Performance of new developed Stilling Basin Model is 49% efficient as compared to USBR VI stilling basin model and the stilling basin length is also reduced by 23%. Thus this model is emerged as the best Stilling Basin Model among all other tested models as it is efficient and economical as compared to USBR VI Stilling Basin Model at zero depth of pipe outlet.